From electrochromic phenomena to energy harvesting and storage—an overview of solid state ionics research at the Institute of Solid State Physics, University of Latvia - Kleperis, Jānis; Gunārs, Bajārs; Grīnberga, Līga; Guntars, Vaivars; Purāns, Juris; Vītiņš, Ģirts; Kučinskis, Gints (Springer, 2023)
Solid state ionics is one of the key research topics of the Institute of Solid State Physics, University of Latvia since its establishment. The research direction included topics ranging from electrochromic phenomena in transition metal oxides through gas sensors and electronic nose to materials for rechargeable battery electrodes and materials for hydrogen energy. By the late 1980s, the institute had become one of the biggest and most prolific solid state ionic centres in the USSR and Eastern Europe and continues to maintain its position among the regional leaders in the field. Regular regional conferences and workshops were organized and some of the published works can be ranked among the pioneering works in the world of science. This extensive historical review summarizes information on the development of solid state ionics, actual research and achievements from establishment of the institute to the present day. Currently many collaborations are ongoing with partners across Europe and beyond in research ranging from battery materials and smart windows for zero energy buildings to hydrogen production, maintaining and growing its strength as key national, regional, and international centre of research excellence in solid state ionics.
G.B. and G.K. acknowledge funding from the Latvian Council of Science (lzp-2020/1–0425) for their contributions in the chapter on Li-ion battery research. Institute of Solid-State Physics, University of Latvia as the Centre of Excellence has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01–2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Solid state ionics; Solid electrolytes; Electrochromic materials; Electrochemical sensors; Hydrogen storage in solids; Photocatalysis; Lithium-ion batteries; Sodium-ion batteries